Codetermination and German Politics - Spiro, Herbert (Relations industrielles / Industrial Relations, 1956)
SummaryThe Author first discusses three forms of codetermination in Germany. He then explains how codetermination came into being in that country, stressing less the ideological factors than the concrete situation which prevailed in Germany after the Second World War. He later describes the actual workings of codetermination in the German iron, steel and coal industries. There follows an evaluation of codetermination by various participants from three viewpoints: economic, sociological, and political.